Psychology of Design. (2019) - Carbon, Claus-Christian
Abstract : Talking about design, most discussions circulate around physical objects or products, around their invention, development, production and marketing. While most modern design approaches do also cover questions pertaining to human interaction, e.g. within user- or human-centred design philosophies, a systematic and fundamental conception of the role and implications that human perception and emo-cognitive processing take with regard to designing physical goods is lacking. Under the umbrella term 'Psychology of Design', I will develop and elaborate on psychological dimensions that are highly relevant to the optimization and evaluation of design. I propagate a general psychological turn in design theory and practice in order to purposefully include not only the top-down processes triggered by context, framing, expectation, knowledge or habituation but also the psychological effects of Gestalt and Zeitgeist. Such psychological effects have the potential to determine whether the very same physical design will be aesthetically appreciated, desired, loved or rejected in the end. Psychology of design has a tremendous influence on the success and sustainability of design by triggering associations and displaying demand characteristics in a multimodal way. The paper is based on fundamental psychological theories and empirical evidences which are linked to applied examples from the world of art and design.